AN OVERVIEW OF THE ROLE OF INTEGRATED HEALTHCARE CENTER CADRES IN PREVENTING STUNTING IN BABIES TODDLER IN CIKUNIR VILLAGE - Danefi, Tupriliany; Agustini, Fenty; Sumartini, Erwina; Hidayani, Wuri Ratna (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
The participation of cadres in the execution of the stunting program aligns with the key principle of addressing stunting in Indonesia, focusing on convergence, coordination, and consolidation of national, regional, and community initiatives. Cadres play a crucial role in promoting child and maternal health by serving as primary sources of health information for mothers. The study aims to examine the contribution of cadres in combating stunting in Cikunir Village, employing a quantitative approach with descriptive methods targeting cadre mothers as the population. Findings indicate that 56 individuals (98.24%) displayed good knowledge, while one person (1.75%) exhibited sufficient knowledge. Additionally, 45 individuals (78.95%) received strong spousal support, with 12 individuals (21.05%) lacking sufficient support. Regarding the performance of Posyandu cadres, 51 individuals (89.47%) demonstrated a commendable role, while 6 individuals (10.53%) displayed inadequate performance. Posyandu cadres are expected to lead the efforts in preventing stunting cases effectivel.